2012
DOI: 10.1002/smj.2021
|View full text |Cite
|
Sign up to set email alerts
|

Top management team nationality diversity and firm performance: A multilevel study

Abstract: This research reexamines the equivocal relationship between top management team (TMT) diversity and firm performance. Combining upper echelons theory with insights from institutional theory, we establish a new, timely dimension of TMT diversity—nationality diversity—and develop an integrated multilevel framework explaining how its performance implications vary across contextual settings. We find that nationality diversity is positively related to performance; and this effect is stronger in (a) longer tenured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
360
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(382 citation statements)
references
References 43 publications
18
360
2
2
Order By: Relevance
“…Informal constraints are culturally-grounded and can thus not be changed through deliberate policies but are passed from one generation to the next and only change gradually in that process (Hofstede, 1991;. They have an enduring impact on executive mindsets (Geletkanycz, 1997) and interpretation and response to strategic issues (Schneider & DeMeyer, 1991;Nielsen & Nielsen, 2013).…”
Section: Informal Institutions: Normative Controlmentioning
confidence: 99%
“…Informal constraints are culturally-grounded and can thus not be changed through deliberate policies but are passed from one generation to the next and only change gradually in that process (Hofstede, 1991;. They have an enduring impact on executive mindsets (Geletkanycz, 1997) and interpretation and response to strategic issues (Schneider & DeMeyer, 1991;Nielsen & Nielsen, 2013).…”
Section: Informal Institutions: Normative Controlmentioning
confidence: 99%
“…Authors following upper echelon tradition have argued that demographic characteristics, such as age, gender, tenure, educational and functional background are indicative of underlying cognitive and affective managerial characteristics that determine the decisions of management teams, which subsequently affect organizational performance [25,26]. Recently upper echelon literature has focused on the heterogeneity of top management teams (TMT), where several authors have shown that heterogeneity provides TMTs with a greater variety of professional perspectives, types of knowledge and decision-making styles [27,28]. This should result in more ideas and more creativity in the development of environmental strategic actions.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This may require the construction of structure configurations with other factors in mind to enhance synergy. The effects of TMT demographics on performance range from positive through non-significant to negative (Nielsen & Nielsen, 2013). Organizational performance gives a broad picture of the TMT and actions of managers whose role in the organization is pivotal (Nielsen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of TMT demographics on performance range from positive through non-significant to negative (Nielsen & Nielsen, 2013). Organizational performance gives a broad picture of the TMT and actions of managers whose role in the organization is pivotal (Nielsen, 2013). TMT demographics are believed to influence the decisions that they make in terms of corporate strategy and organizational structure adopted that in turn will produce outcomes, notably organizational performance (Bagire, 2012).…”
Section: Introductionmentioning
confidence: 99%